2004
DOI: 10.1080/13625180400017768
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at traditional contraceptive use in Turkey

Abstract: Withdrawal is the main method used amongst couples in Turkey to prevent pregnancy. Discontinuation of use is most likely to be due to the desire to become pregnant or failure of the method. Withdrawal users are less likely to switch to another contraceptive method; however, among users who do switch, they will most likely switch to a modem method. The strongest three determinants that predict withdrawal use are using withdrawal as one's first method, the woman's age, and the husband's education. The woman's wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
2
9
2
5
Order By: Relevance
“…There was a significant relationship between age and contraceptive method, which is in line with our study (13). The results of Mehryar et al, Yosefzade and Ergocmen et al studies showed that there was a significant relationship between age and contraceptive method (7,15,16).…”
Section: Discussionmentioning
confidence: 92%
“…There was a significant relationship between age and contraceptive method, which is in line with our study (13). The results of Mehryar et al, Yosefzade and Ergocmen et al studies showed that there was a significant relationship between age and contraceptive method (7,15,16).…”
Section: Discussionmentioning
confidence: 92%
“…16,17 Cinselliğin çiftler arasında ve toplumda rahat bir şekilde konuşulamaması, özellikle ark.n etkisi ile yöntem seçme olasılığını ve geri çekme yönteminin erkeklerin çoğunlukla ilk kullandığı yöntem olmasını beraberinde getirmektedir. 3,13,18 Bu durumda, ilk yöntem seçiminin bir sonraki AP yöntem seçiminde çok önemli olduğu görünmektedir. 3,11 Altay ve Görener, Türki-ye'de evli erkekler tarafından en yaygın bilinen ve kullanılan yöntemlerin erkeklerin kullandık-ları yöntemler olduğunu belirlemişlerdir.…”
Section: Discussionunclassified
“…3,13,18 Bu durumda, ilk yöntem seçiminin bir sonraki AP yöntem seçiminde çok önemli olduğu görünmektedir. 3,11 Altay ve Görener, Türki-ye'de evli erkekler tarafından en yaygın bilinen ve kullanılan yöntemlerin erkeklerin kullandık-ları yöntemler olduğunu belirlemişlerdir. 6 Buna ilave olarak, Ergöçmen ve ark., erkeklerin ihtiyaçlarını göz önünde bulunduran aile planlaması programlarının kız ve erkekleri içine alan tüm gençler için AP seçeneklerini içine alan evlilik öncesi danışmanlık hizmetinin önemini vurgulamışlardır.…”
Section: Discussionunclassified
See 2 more Smart Citations